Investigation of the Relationship Between the Anti-Oxidant Effect, Brand Trust, Healthiness, and Intention to Purchase Propolis Products: The Moderating Effect of Nutritional Disclosure - Min Gyung Kim; Ye Kang Kim; Joonho Moon (Applied Sciences)
Propolis market is growing, and such growth suggests the importance of understanding consumer behavior. Hence, the aim of this research is to explore the relationship between the anti-oxidant effect, brand trust, healthiness, and consumers’ intention to purchase propolis products. A secondary objective is to examine the moderating role of nutrition disclosure. Survey participants were recruited via the Clickworker platform, yielding 305 valid observations for statistical analysis. The Hayes Process Macro Model 7 was employed to test the research hypotheses. The results indicated that the anti-oxidant effect is positively associated with both healthiness and intention to purchase. Moreover, the findings showed that brand trust is positively related to healthiness and intention to purchase. Additionally, the results disclosed the significant moderating effect of nutrition disclosure on the impact of the anti-oxidant effect and brand trust on healthiness based on the heuristic effect as theoretical underpinning. This research sheds light on the literature by clarifying the relationship between five attributes in the domain of propolis products.